Effect of Machining Process Parameters on Acceleration Signal in Determining Surface Quality of Milling Process at Ductile Iron - Norlida, Jamil; A. R., Yusoff (2019)
The present work studies the effect of machining parameters for deter-mining surface quality during milling process of ductile iron under different lu-brication conditions. It was conducted by adopting direct and indirect measure-ment using two accelerometers with coated and uncoated tool. The experiment data was collected by inputs of spindle speed, feed rate, axial-radial depth of cut, and MQL flow rate. The response in term of vibration signal was measured and extracted from time series data into kurtosis and skewness analyses. For direct measurement, surface qualities from experimental configuration of workpiece were measured using roughness tester for verification and comparison. Alterna-tively, the result verified the different effect of machining process parameters contributes to different surface quality based on kurtosis and skewness analyses for the indirect measurement.